A generic curriculum development model for the biomedical physics component of the educational and training programmes of the non-physics healthcare professions - Caruana, C. J.; Karenauskaite, V.; Mornstein, V.; Vano, E.; Pace, E.; Lammertsma, A. A.; Maas, A. J.J.; Bert, Christoph; Byrne, B.; Colgan, N.; Essers, M.; Isidoro, J.; et al. (Physica Medica, 2021)
The objective of the study was the construction of a generic curriculum development model for the use of biomedical physics (BMP) educators teaching the non-physics healthcare professions (HCP) in Europe. A comprehensive, qualitative cross-sectional Europe-wide survey of the curricula delivered by BMP in Faculties of Medicine and Health Sciences (FMHS) was carried out. Curricular content was collected from faculty web-sites, curricular documents and textbooks. The survey data was supplemented with semi-structured interviews and direct observation during onsite visits. The number of faculties studied was 118 from 67 universities spread all over Europe, whilst the number of onsite visits/interviews was 15 (geographically distributed as follows: Eastern Europe 6, North Western Europe 5, and South Western Europe 4). EU legislation, recommendations by European national medical councils, educational benchmark statements by higher education quality assurance agencies, research journals concerning HCP education and other documents relevant to standards in clinical practice and undergraduate education were also analyzed. Best practices and BMP learning outcomes were elicited from the curricular materials, interviews and documentation and these were subsequently used to construct the curriculum development model. A structured, comprehensive BMP learning outcomes inventory was designed in the format required by the European Qualifications Framework (EQF). The structures of the inventory and curriculum development model make them ideally suited for use by BMP involved in European curriculum development initiatives for the HCP.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Biomedical physics; Curriculum development; Healthcare professions; Medical devices